Information-Seeking at a Caregiving Website: A Qualitative Analysis - Kernisan, Leslie P; Sudore, Rebecca L; Knight, Sara J (JMIR Publications, 2010)
BackgroundThe Internet is widely used for health information, yet little is known about the online activity of family caregivers of elders, a rapidly growing group. In order to better understand the online information-seeking activity of "e-caregivers" and other visitors at a caregiving website, we undertook a qualitative analysis of survey data from a website marketed as a comprehensive resource for adults caring for aging parents. ObjectiveThe objectives were to better understand what types of information are sought by those visiting a website focused on elder-care issues and to identify overarching themes that might inform future development of Internet resources related to caregiving and aging. MethodsFrom March 2008 to March 2009, a 5-question pop-up survey was offered 9662 times and completed 2161 times. For 1838 respondents, included was a free text answer to the question "What were you looking for?" and 1467 offered relevant and detailed responses. The survey also asked about satisfaction with the site, gender of the respondent, and relationship to the individual being cared for. Content analysis was used to develop a coding dictionary, to code responses into information-seeking categories, and to identify overarching themes. ResultsOf the respondents (76% of whom were female), 50% indicated they were caring for parents, 17% for themselves only, and 31% for others. Over half (57%) reported finding what they were looking for, and 46% stated they were extremely likely to recommend the website. Frequently mentioned information-seeking categories included "health information," "practical caregiving," and "support." Respondents also requested information related to housing, legal, insurance, and financial issues. Many responses referred to multiple comorbid conditions and complex caregiving situations. Overarching themes included (1) a desire for assistance with a wide range of practical skills and information and (2) help interpreting symptoms and behavior, such as knowing what life impacts to expect over the course of a health condition or treatment. ConclusionVisitors to a website targeting adults caring for aging parents reported seeking both general information on caregiving and specific assistance with the complex custodial, medical, emotional, and financial aspects of caregiving. Visitors requested both information to build caregiving skills as well as assistance in interpreting and knowing what to expect from symptoms, health conditions, and changes in behavior and relationships. Many desired communication with and support from other caregivers. Health care providers and eHealth developers should expect that many caregivers of elders are using the Internet as a resource. Further research and development is needed to fully realize the Internet's potential for education and support of caregivers.